On features of deoxidization of CsI melt with zirconium getter - Datsko, Yu.N.; Rebrova, T.P.; Cherginets, V.L.; Naumenko, V.A.; Rebrov, A.L.; Mateychenko, P.V.; Vjunnik, I.N. (Functional Materials, 2016)
Interaction of Zr getter with oxygen-containing admixtures being most abundant in molten alkali metal iodides (deoxidization) is studied. Reaction of Zr with oxide ions (in form of the corresponding alkali metal oxide) is characterized by very negative enthalpy and Gibbs energy values that make the deoxidization process very favorable. Practically the interaction leads to decrease of O²⁻ concentration by a factor of ca. 6. Interaction of Zr with carbonate ions is shown both by the calculations and by experiment Ґй lead to the formation of carbon particles (suspension) in the melts that causes certain limitations of the getter treatment for the purification of practically used growth iodide melts.